FENOMENA SASTRA CYBER: TREN MENULIS CERITA SASTRA DALAM BINGKAI MEDIA SOSIAL - Iqbal Wahyudi; Rianna Wati (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2021)
Increasingly advanced technology makes it easy for people to communicate and obtain information. Today's literature adds to its medium that is not just print but stepping into the realm of cyber. Not only literary works, several literary communities that were formed also showed themselves in social media. This study aims to see the trend of writing literary stories on social media through invitations to write and in the cyber literary community. The method used in this research is descriptive qualitative. The object of research is the literary community on Facebook and Twitter, and an invitation to tell stories on Instagram. The results of this study are the phenomenon of cyber literature on the trend of writing fiksimini, pentigraphs and stories uploaded with pictures of the Fiksimini Community, Kampung Pentigraf Indonesia, and # 30haribercerita.